EVALUASI TAMAN RENUNGAN BUNG KARNO SEBAGAI TAMAN BERSEJARAH KOTA ENDE - Bato, Edmundus; Djoko, Riyanto; Nailufar, Balqis (Universitas Tribhuwana Tunggadewi, 2019)
City Park is a Green Open Space. In general city parks are made not only for beauty and social functions for the city, but city parks can also be used as a specific function, namely as a historical park in accordance with the history that has ever happened. Bung Karno's Reflection Park is still not in accordance with the criteria as a historical park. For this reason, this research was conducted to identify and analyze the value of Bung Karno Reflection Park as a historical park and the evaluation was carried out by looking at the criteria of the historic park and the public perception of the park. The results of the analysis questionnaire using descriptive analysis were then evaluated using the KPI (Key Performance Index) method. Based on the results of the inventory and evaluation based on criteria from historic parks, it can be concluded that Bung Karno's Reflection Park has not yet met the criteria of a historic park. Taman kota merupakan Ruang Terbuka Hijau. Secara umum taman kota dibuat tidak hanya sekedar untuk keindahan dan fungsi sosial bagi kota, namun taman kota juga dapat digunakan sebagai fungsi yang spesifik, yaitu sebagai taman bersejarah sesuai dengan sejarah yang pernah terjadi. Taman Renungan Bung karno masih belum sesuai dengan krtiteria sebagai taman bersejarah. Untuk itu penelitian ini dilakukan untuk mengidentifikasi dan menganalisis nilai Taman Renungan Bung Karno sebagai taman bersejarah dan Evaluasi dilakukan dengan melihat kriteria dari taman bersejarah dan presepsi masyarakat terhadap taman. Hasil kuisoner analsis menggunakan analisis deskriptif kemudian di evaluasi menggunakan Metode KPI (Key Perfomance Index). Berdasarkan hasil inventarisasi dan evaluasi berdasarkan kriteria dari taman bersejarah dapat simpulkan bahwa Taman Renungan Bung Karno belum sesuai dengan kriteria sebagai taman bersejarah.